Interpersonelle Verteilungswirkungen aus dem Angebot öffentlicher haushaltsbezogener Infrastruktur: Eine empirische Analyse für ausgesuchte Bereiche in Deutschland zu Beginn der 90er Jahre - Ivo Bischoff; Stephan Heck (Justus-Liebig-Universität Gießen, Fachbereich Wirtschaftswissenschaften, 2001)
In Germany the government spends substantial resources on the provision of infrastructure. Apart from firms, private households are very often the beneficiaries. This paper analyses the impact of the supply of household-related public infrastructure on the personal income distribution within a county. It concentrates on the short-term distributional effects resulting from the use of the infrastructure. A theoretical overview on the relevant factors that determine these effects is followed by an empirical study. Based on household data from the Time Budget Survey 1991/1992 of the Statistisches Bundesamt, the study analyses the distributional effects of the publicly provided infrastructure in the fields of sports, leisure and cultural affairs in Germany in the beginning of the 1990s. The benefits in money's worth that the households draw from using this infrastructure are found to reduce income inequality.
Keywords: 330; Einkommensverteilung; Einkommensumverteilung; Verteilungspolitik; Kommunale Infrastruktur; Infrastruktur; Interpersoneller Nutzenvergleich; Deutschland